Study of Mechanical Characteristics for Polymer Composite Reinforced by Particles of (Al2O3) or (Al) - Ataiwi, Ali Hussein; Uleiwi, Jawad Kadhim; elIa, Saad M. (Al-Khwarizmi Engineering Journal, 2007)
A particulate polymer composite material was prepared by reinforcing with the Aluminum Oxide (Al2O3) or Aluminum (Al) metallic particles with a particle size of (30) µm to an unsaturated Polyester Resin with a weight fraction of (5%, 10%, 15%, 20%). Tensile test results showed the maximum value of elastic modulus reached (2400MPa.) in the case of reinforcing with (Al) particles with weight fraction (20%) and (1500 MPa.) in the case of reinforcing with (Al2O3) particles of the same weight fraction. When the impact and the flexural strength tests were done, the results showed that flexural strength (F.S), maximum shear stress (τmax), impact strength (Gc) and fracture toughness (Kc) were increased with the increase of weight fraction, where the results of the samples of (Al) particles were higher than that of (Al2O3) particles reinforced at a weight fraction of (20%) at ratios of (45.43%, 45.45%, 25%, 41%) respectively. While the hardness of the samples reinforced with (Al2O3) particles was higher than that reinforced with (Al) particles with a ratio of (2.82%) at a weight fraction of (20%).